The Smart city vision: The internet-of-postal-things (iopt) approach - Maria PAVLOVSKAYA; Olga KONONOVA (Smart Cities and Regional Development Journal)
Nowadays the popular Smart city concept focuses on the quality improvement of a citizenâ€™s life by using the information and communication technology. Frequently Smart city projects are stalled at the initial stages due to insufficient data volume. Meanwhile, state Postal services remain outside the Smart cities concepts and models, despite the available resources to handle big data. This research is aimed to highlight the significance of Postal services involvement in effective data collection, storage and aggregation. The study refers to the international sources and considers a high-level Smart city architecture and data-driven approach; gives an analysis of researches results and case studies of international Postal services in the field of socially significant initiatives; describes the functions and assets of the Russian Post. The paper presents identified opportunities of Postal services participation in the processes of Smart city projects, describes an applicability of the approach to the Russian realities. It also provides the models of Postal services involvement in Smart city projects and meta-model of the data which collection is possible using the Russian Post assets. The main idea is to integrate urban information systems and the Postal services assets for more efficient and ubiquitous data collection, which entails additional quality in public services. The integration will improve the city authorities results, ensure the safety of information resources, i.e. will help all participants to achieve their goals. Such approaches are named Internet of Postal Things. The relevance of the work is further conditioned by increased government activity in Smart cities development in Russia, which is caused by â€œRussian Digital Economyâ€ document release, where the Smart city direction is allocated. In accordance with the document city authorities, scientific and business communities started the mega-project â€œSmart city St. Petersburgâ€ where the described research results will be used.